The Ethnic Kocika Marriage Of The Laporo Community From The Perspective Of Islamic Law - Irma Purnamayanti; Ian Narwati Irisi (AIQU: Journal Multidiscipliner of Science, 2025)
This study examines the local wisdom of the Laporo ethnic group, namely the tradition of determining auspicious days, known as kocika in the Ciacia language. This study is then linked to an Islamic legal perspective. The research location is in Bugi Village, Sorawolio District, Baubau City. The focus of this study is (1) the process of calculating kocika for marriage and (2) the Islamic legal perspective on kocika for marriage. This thesis is a qualitative study with an empirical approach. Data collection techniques used were interviews and literature review. Data analysis was conducted using descriptive analysis. The results of this study indicate that, first, the process of calculating kocika (determining auspicious days) for marriage begins with a family meeting, the main benchmark of which is knowing the woman's menstrual period and estimated fertile period. Second, the Islamic legal perspective on kocika, or choosing an auspicious day for marriage, is permissible as long as it does not adhere to the belief that marriages conducted during months forbidden according to the Laporo calendar are bad, as according to Islam all days are good and none are bad. Kocika is an effort to find an auspicious day for marriage and Maslahah mursalah, or utilizing and avoiding harm for the sake of the objectives of sharia. This is intended as an effort to choose a pleasant day that provides benefits to society.